Vimentin reactivity in renal oncocytoma: immunohistochemical study of 234 cases - Hes, Ondrej; Michal, Michal; Kuroda, Naoto; Martignoni, Guido; Brunelli, Matteo; Lu, Yi; Adley, Brian P; Alvarado-Cabrero, Isabel; Yang, Ximing J (Archives of pathology & laboratory medicine, 2007)
CONTEXT: The expression of vimentin in benign renal oncocytomas has been controversial. However, this is of clinical significance because immunostains may be used in differential diagnosis of renal tumors on limited biopsy specimens. Using different staining and analysis methods, we studied vimentin immunoreactivity in a large series of renal oncocytomas with a special emphasis on the immunoreactivity patterns. OBJECTIVE: Immunohistochemical expression of vimentin has been used in the differential diagnosis of renal epithelial neoplasms. Although typically expressed in most renal cell carcinomas, the immunoreactivity of this intermediate filament in renal oncocytomas has been controversial. DESIGN: We studied vimentin immunoreactivity in a large series of 234 renal oncocytomas using 2 staining methods as well as manual and automated imaging analyses. RESULTS: We found that the focal vimentin immunoreactivity can be seen in most (72.6%) renal oncocytomas with vimentin-positive tumor cells usually found in the edge of a central scar or in small clusters scattered throughout the tumor. Computer-aided imaging analysis using ChromaVision Automatic Cellular Imaging System II confirmed the difference in vimentin immunoreactivity between oncocytoma and other renal neoplasms. CONCLUSIONS: Our study of vimentin immunohistochemistry in a series of renal oncocytomas, which to our knowledge is the largest ever published, showed focal vimentin positivity detected in most oncocytomas. Because the vimentin staining patterns in renal oncocytomas are different from those seen in clear cell or papillary renal cell carcinomas, we consider vimentin staining to be helpful in the differential diagnosis of oncocytoma from other renal tumor mimics. Furthermore, strong vimentin positivity in a renal cell neoplasm does not exclude the diagnosis of renal oncocytoma, particularly in a limited biopsy specimen.
Keywords: Adenoma, Oxyphilic; diferenciální diagnóza; Diagnosis, Differential; oxyfilní adenom; Image Processing, Computer-Assisted; Immunohistochemistry; nádory ledvin; Humans; Vimentin; vimentin; Kidney Neoplasms; lidé; počítačové zpracování obrazu; imunohistochemie